A solar-driven lumped SOFC/SOEC system for electricity and hydrogen production: 3E analyses and a comparison of different multi-objective optimization algorithms - Cao, Yan; parikhani, Towhid (Journal of cleaner production, 2020)
In this paper, a plant consisting of a solid oxide fuel cell and solid oxide electrolysis cell is proposed for power provision based on solar energy. In this system, water enters the solid oxide electrolysis cell and is split into H2 and O2 through the utilization of the generated power by the photovoltaic panels. The produced hydrogen is stored and sent to the solid oxide fuel cell for clean and consistent power generation. The required hydrogen of the fuel cell is measured for 24 h and the electrolysis and photovoltaic units are designed in such a way to satisfy the demand of the fuel cell while the surplus hydrogen is considered for sale. A sensitivity analysis is also conducted on the system to assess the impact of vital parameters on output power, system efficiency, total product cost and total cost rate, total exergy destruction, and payback period. Furthermore, multi-criteria optimization is applied to the system utilizing various optimization algorithms. The outcomes demonstrate that the maximum amount of exergy destruction occurs in the photovoltaic system. The results of the parametric evaluation illustrate that the payback period of the plant can reduce to 7 years when surplus hydrogen is 4 times higher than the required H2 of the fuel cell. Furthermore, higher current densities of the SOEC system can reduce the efficiencies while increasing the payback period, so lower current densities would be more suitable. Also, there would be a local optimum point in terms of total product cost and net power outlet with the current density of the SOFC system. The optimization findings indicate that PESA-II is the most suitable algorithm for this particular system as it results in more suitable optimum points that are closer to the ideal point. In addition, at the final optimum solution point concluded by the LINMAP method, the exergy efficiency of the system would be 62% and the total cost rate is 1.297 $/h. •A novel solar driven lumped SOFC/SOEC is proposed for power and H2 production.•A parametric study is performed to assess the effect of input variables.•Energy, exergy, exergoeconomic analyses and multi-objective optimization are applied.•Different optimization algorithms are compared based on Taylor diagram.